Digital Frontiers in Life Sciences: The Transformative Role of Computing in Modern Biology - V. Basil Hans (International Journal of Bioinformatics and Computational Biology, 2026)
The integration of computers in the biological sciences has revolutionized research and experimentation, facilitating advancements in areas such as genomics, bioinformatics, systems biology, and ecological modeling. The ability to process vast amounts of biological data efficiently has transformed how scientists study complex biological systems and phenomena. Computational tools enable the analysis of DNA sequences, protein structures, metabolic pathways, and ecological dynamics, which were previously beyond the reach of traditional laboratory methods. This article explores the role of computers in biological sciences, discussing key technologies, software, and algorithms that support modern biological research. It highlights the importance of computational biology in predictive modeling, drug design, personalized medicine, and the development of more sustainable agricultural practices. As biological data continue to expand, the synergy between computational tools and biological research will remain essential in addressing global challenges in health, ecology, and biotechnology.
Keywords: DNA sequences; biotechnology; computational biology; genetic data; genomics; software